2001
DOI: 10.1038/labinvest.3780239
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Significance of Aneuploidy in the Prognostic Assessment of Colorectal Cancer

Abstract: SUMMARY:The aberrant content of DNA, or aneuploidy, is a hallmark of tumor cells and may be associated with malignant potential. Based on the hypothesis that aneuploidy, as a form of genetic instability, results in an increased capability to generate cell heterogeneity, we investigated whether a comprehensive assessment of aneuploidy extent and degree might be a reliable indicator of tumor aggressiveness. DNA content was determined by flow cytometry in the infiltrating front of 131 paraffinembedded primary col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In these 25 studies, it was observed that the duration of followup was inaccurate or did not reach five years after surgical treatment. Nineteen studies 29,48,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] were excluded because of impossible data extraction. In these studies, survival data tables or curves at fiveyear follow-up were not available or absolute death numbers were available but the group size was not determined at the beginning of follow-up or after five years.…”
Section: Discussionmentioning
confidence: 99%
“…In these 25 studies, it was observed that the duration of followup was inaccurate or did not reach five years after surgical treatment. Nineteen studies 29,48,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] were excluded because of impossible data extraction. In these studies, survival data tables or curves at fiveyear follow-up were not available or absolute death numbers were available but the group size was not determined at the beginning of follow-up or after five years.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that an example of transformation to a near tetraploid state has been described in tissue culture of Barrett's epithelium, which was transfected with hTERT (Corinna et al, 2003). This transformation coupled with repeated exposure to DNA-damaging agents may drive a malignant process to complex aneuploidy with a consequent poor prognosis (Risques et al, 2003).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…Generally, a more detailed assessment—for example, using array comparative genomic hybridisation (arrayCGH)—is impractical for large series. Nonetheless, many studies have reported that CIN+ measured by flow cytometry confers a worse prognosis; however, this observation is neither universal5 6 nor always significant 79. Consequently, it has been argued consistently that measuring CIN does not add further prognostic information to standard pathological and histological staging 10 – 13.…”
mentioning
confidence: 99%